Large‐Area Growth of MoS2/WS2 Heterostructures by a Sequential Atomic Layer Deposition and Spin‐Coating Approach. Issue 31 (20th September 2022) - Pareek, Devendra; Gonzalez, Marco A.; Grewo, Nedal; Janßen, Marten L.; Arunakiri, Kumarahgiri; Alimi, Kayode Luqman; Silies, Martin; Parisi, Jürgen; Gütay, Levent; Schäfer, Sascha
Abstract: Despite the plethora of intriguing phenomena observed in heterostructure stacks of 2D transition metal dichalcogenide (2D‐TMDC) flakes, their application in functional devices is still hampered due to the lack of reliable growth methodologies for large‐area heterostructures. Here, a scalable process for obtaining as‐grown transition metal di‐chalcogenide heterostructures by a combination of atomic layer deposition of monolayer MoS2 and solution‐based processing of ultrathin WS2 is presented. Spatially uniform optical and electrical characteristics of the individual TMDC layers and heterostructures are demonstrated down to micrometer length scales using Raman and photoluminescence spectroscopy, and light‐beam‐induced current measurements. An enhanced photogenerated current is observed for lateral MoS2 –MoS2 /WS2 heterostructures demonstrating the suitability of this approach for the preparation of functional devices. Abstract : A facile process for the growth of large‐area transition metal dichalcogenide heterostructures is demonstrated. Spectroscopic mapping confirms the uniform characteristics down to the micrometer scale. Strong photo‐response is observed on lateral MoS2 –MoS2 /WS2 heterostructures.